Q. 55.0( 1 Vote )

Find fog (2) and

Answer :

We have, f: R R given by f(x) = x2 + 8 and


g : R R given by g (x) = 3x3 + 1


fog(x) = f (g(x)) = f (3x3 + 1)


= (3x3 + 1)2 + 8


fog(2) = (3 × 8 + 1)2 + 8 = 625 + 8 = 633


Again,


gof(x) = g(f(x)) = g(x2 + 8)


= 3(x2 + 8)3 + 1


gof(1) = 3(1 + 8)3 + 1 = 2188


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Fill in theMathematics - Exemplar

Let f : [2, ∞) <sMathematics - Exemplar

Let f : N Mathematics - Exemplar

Fill in theMathematics - Exemplar

Let f :R →<Mathematics - Exemplar

Let f : [0, 1] <sMathematics - Exemplar

Which of the follMathematics - Exemplar